AS CONTRIBUIÇÕES DOS EDUCADORES BOLCHEVIQUES NA CONCRETIZAÇÃO DE POLÍTICAS EDUCACIONAIS NA EDUCAÇÃO SOVIÉTICA - Ferreira, Caroline de Melo (2014)
This work linked to the Educational Policy and Management line articulates the ongoing research and examines the historical period from 1917 to 1930, when Bolsheviks educators influenced the Soviet education in the process of building the revolutionary society. This important historical context generated our interest on the topic, that led us to have contact with a period restricted by educational discussions. Thus, we intend to investigate who were the educators who contributed to the advancement of Soviet education, which was thought by them and which ideas about education were realized through educational policies. Through a study of the revolutionary era in Russia, we intend to present the educational principles of Moisey Mikhaylovic Pistrak (1888-1940), Nadejda Konstantinovna Krupskaya (1869-1939) and Anatóli Lunacharsky (1875-1933). We will try to determine whether the proposals of some of these educators (or all) for the time actively contributed to the establishment of a socialist educational practice, based in marxism. Each one with its practices and studies helped building what is known in history as a socialist pedagogy, based on the collective idea linked to the broader movement for social transformation. The hypothesis about the practical importance of these authors will be investigated throughout the work. The research tries to contribute to a discussion about the possible values in contemporary education, which ideally should value the work of the human being and humanitarian relations between men. However, in the local context we did not have access yet to a lot of studies related to the topic. Despite this fact, the research is justified as an analysis of the historical period known for its importance to the developments in contemporary society. Part from the assumption that in the post-revolutionary period happened great intellectual and cultural ferment, generating several different proposals in the school organization area, the pedagogical action, the relationship between school-society, school-production units, socialist education and citizenship, etc. During the research, for each educator to be studies, it was necessary to find in their works the presence of four relevant themes in the Soviet debate that period: the new Soviet society (dominant role of the state, the decline in the role of church and family, claim the economic system of participation in education); the organization of teaching through problem (modular system) approach; the process of cultural revolution and the construction of the new man; and the polytechnic. To substantiate the issues, it is necessary to characterize the position of educational thought and action of each author. In addressing the issues we will also seek other authors interested in the Soviet education and the doctrinal trends in the field of education. We therefore conclude that the research will contribute to academia, to study of pedagogy and educational policy, and to understanding the thinking of Bolsheviks educators.